2011
DOI: 10.1007/s11284-011-0898-0
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and decomposition potential of endophytes in leaves of a Cinnamomum camphora plantation in China

Abstract: This study was carried out to improve our understanding of the diversity and decomposition potential of endophytes in the leaves of Cinnamomum camphora trees grown in a subtropical region of China. We isolated and identified endophytic fungi from senescent leaves of C. camphora and tested their role in decomposition through pure‐culture and pre‐colonization. A total of 2,861 endophytic fungi isolated from 69 leaves of C. camphora were grouped into 39 taxa comprising 36 Ascomycetes and 3 Basidiomycetes based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 51 publications
1
39
0
Order By: Relevance
“…Some endophytic species could decompose Cinnamomum camphora leaf litter in pure Fig. 2 Proposed schema of biotransformation of 2-hydroxy-1,4-benzoxazin-3-one (HBOA) and 2-benzoxazolinone (BOA) by Chaetosphaeria sp., Gliocladium cibotii, Gibberella pulicaris, and Monographella cucumerina (Zikmundová et al 2002) culture (He et al 2012). During biodegradation of the litter, endophytic fungi colonize initially within the plants and facilitate the actio of the saprophytic fungi through antagonistic interaction, thus increasing litter decomposition (Nair and Padmavathy 2014).…”
Section: Nutrient Cyclingmentioning
confidence: 99%
“…Some endophytic species could decompose Cinnamomum camphora leaf litter in pure Fig. 2 Proposed schema of biotransformation of 2-hydroxy-1,4-benzoxazin-3-one (HBOA) and 2-benzoxazolinone (BOA) by Chaetosphaeria sp., Gliocladium cibotii, Gibberella pulicaris, and Monographella cucumerina (Zikmundová et al 2002) culture (He et al 2012). During biodegradation of the litter, endophytic fungi colonize initially within the plants and facilitate the actio of the saprophytic fungi through antagonistic interaction, thus increasing litter decomposition (Nair and Padmavathy 2014).…”
Section: Nutrient Cyclingmentioning
confidence: 99%
“…Also, some endophytes may cause diseases in their hosts. For example, Colletotrichum gloeosporioides has often been encountered as endophyte in many studies (Hata et al, 2002;Hata and Sone, 2008;Osono and Hirose, 2009;He et al, 2012), but it may also cause anthracnose, black canker and leaf spot in host plants under certain conditions (Spiers and Hopcroft, 2007;Miyara et al, 2008;Embaby et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…What is the fate of the endophytes after their hosts died, which has made the ecologists to be lost in thought for very long time, and encourages the ecologists to pay close attention to this field. Many endophytes had been found as pioneer colonizers in litter decomposition (Müller et al, 2001;Kumaresan and Suryanarayanan, 2002;Osono, 2003Osono, , 2006Korkama-Rajala et al, 2008;Fukasawa et al, 2009;He et al, 2012;Peršoh et al, 2013;Unterseher et al, 2013;Vo ríšková and Baldrian, 2013), and they had also often been found in the litter layer (Mitchell et al, 1978;Livsey and Barklund, 1992;Lindahl et al, 2007;Unterseher et al, 2013). Endophytic fungi can take the priority over other saprophytic fungi from the beginning of litter decomposition by colonizing plant tissue when it is still living (Thormann et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…None of these have been recorded as causing disease symptoms in adult parkinsonia in available literature, however many of these species have previously been recorded as endophytes in other plant species (Sakayaroj et al 2010;Xing et al 2011;He et al 2012;Loro et al 2012) supporting the finding of their presence as endophytes in parkinsonia. Only two of the species found (Fusarium equiseti and Alternaria alternata) matched two of the 16 species previously found in parkinsonia seeds in India (Sahu & Agarwal 2002a, 2002b.…”
Section: Discussionmentioning
confidence: 87%